2022
DOI: 10.3389/fcvm.2022.1006789
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in hypertension among people living with HIV after initiation of antiretroviral therapy

Abstract: BackgroundHypertension is common in people living with HIV (PLWH) on antiretroviral therapy (ART). In the general population and in experimental animal models, the incidence of hypertension is greater in males than in females, especially during the premenopausal period. However, it is not known whether there are sex differences in hypertension associated with HIV and ART, and the factors contributing to incident hypertension among PLWH have not been well characterized. In this study, we aimed to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…It is worth noting that the prevalence of SSBP is higher in women than in men across all ethnicities and increases with age in both genders, raising the question of whether a cortisol-dependent pathway plays a role in sex and age related differences in SSBP. 44,45 Previous research has indicated that cortisol levels are higher in men who are salt-sensitive compared to those who are salt-resistant 46 . However, to date, there are limited studies that investigate gender differences in cortisol metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the prevalence of SSBP is higher in women than in men across all ethnicities and increases with age in both genders, raising the question of whether a cortisol-dependent pathway plays a role in sex and age related differences in SSBP. 44,45 Previous research has indicated that cortisol levels are higher in men who are salt-sensitive compared to those who are salt-resistant 46 . However, to date, there are limited studies that investigate gender differences in cortisol metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Certain types of exercise, especially those involving highintensity or sustained effort, may pose challenges for women who have asthma, COPD, or other respiratory illnesses. 50,51 Nevertheless, there is a prevailing belief that individuals with COPD and additional medical conditions can achieve substantial and meaningful enhancements in their functional exercise capacity and overall health condition with the implementation of an exercise-based pulmonary rehabilitation program. 51…”
Section: Respiratory Conditionsmentioning
confidence: 99%
“…The specific pathogenesis of high blood pressure-induced heart disease remains unclear. 14 Therefore, understanding the risk factors and exploring its pathogenesis are crucial for preventing its occurrence. To evaluate the coverage of knowledge integration of the CBK system, we took hypertensive heart disease as an example and compared the risk factors identified by the Institute for Health Metrics and Evaluation (IHME) with those extracted in CBK system.…”
Section: Case Query 1: Identifying Risk Factors and The Causal Paths ...mentioning
confidence: 99%